Odpowiedź:
zad 19
a)
(3 - x)/2 + (x + 2)/2 = 1/2 | * 2
3 - x + x + 2 = 1
5 ≠ 1
L ≠ P
Równanie sprzeczne x ∈ ∅ (zbiór pusty)
b)
1/4x - (x - 1)/4 = 1/4 | * 4
x -x + 1 = 1
x - x = 1- 1
0 = 0
Równanie tożsamościowe , spełnia je każda wstawiona za x
x ∈ R
c)
(x + 1)/2 + (2x - 2)/3 = (2x - 4)/6 | * 6
3(x + 1) + 2(2x - 2) = 2x - 4
3x + 3 + 4x -4 = 2x - 4
7x - 1 = 2x - 4
7x - 2x = - 4 + 1
5x = - 3
x = - 3/5
d)
(2x + 3)/3 + (x - 4)/5 = (3x + 5)/10 | * 30
10(2x + 3) + 6(x - 4 ) = 3(3x + 5)
20x + 30 + 6x - 24 = 9x + 15
26x + 6 = 9x + 15
26x - 9x = 15 - 6
17x = 9
x = 9/17